2018
DOI: 10.1097/md.0000000000009583
|View full text |Cite
|
Sign up to set email alerts
|

The clinical manifestation, survival outcome and predictive prognostic factors of 137 patients with primary gastrointestinal lymphoma (PGIL)

Abstract: This retrospective study aimed to investigate clinical characteristics and prognostic factors in patients with primary gastrointestinal lymphoma (PGIL) of Chinese population.From January 2001 to December 2015, 137 patients diagnosed with PGIL were recruited. The clinical features, treatment, and follow-up information were analysed.The median patient age was 62.3 years. With 18.47 months follow-up, the 2-year progress-free survival and overall survival rate was 74.9% and 75.5%, respectively. The overall respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Our study also indicates that small intestinal lesions (mainly terminal ileum lesions) are more common in MCL cases. Several studies have reported the features of GI MLs (such as incidence rate, subtype frequency, localization, and prognosis) (19)(20)(21)(22). They revealed that the prognoses of ML cases involving overlapping lesions and advanced stages were significantly poorer than those of ML cases involving single lesions and early stages (9,14,23).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also indicates that small intestinal lesions (mainly terminal ileum lesions) are more common in MCL cases. Several studies have reported the features of GI MLs (such as incidence rate, subtype frequency, localization, and prognosis) (19)(20)(21)(22). They revealed that the prognoses of ML cases involving overlapping lesions and advanced stages were significantly poorer than those of ML cases involving single lesions and early stages (9,14,23).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective multicenter clinical study of 299 B-cell lymphoma cases revealed IPI ≥2 to be an independent prognostic factor for worse OS ( 32 ). However, Shi et al study of 137 patients found that there was no apparent prognostic significant correlation between IPI and survival ( 33 ). Lugano staging system was also used to modify the IPI for primary GI NHL ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, age was not found to have significant relation in responders and nonresponders which is in contradiction to published facts that age is considered as a negative predictor of response. [14] BMI is considered as a better predictor of response and overall survival (OS) in patients with lymphoma. [15] Our data did not show any impact of BMI in responders and nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in contradiction to published findings revealing the poor impact of bulky disease, staging, and extranodal involvement on PFS. [14] HL responders were found to be significantly younger with a higher decline in BMI as compared to NHL responders. This could be secondary to wider range of BMI at baseline in HL patients.…”
Section: Discussionmentioning
confidence: 99%